2020
DOI: 10.4103/aca.aca_52_19
|View full text |Cite
|
Sign up to set email alerts
|

Does the endotracheal tube cuff pressure increases with transesophageal probe insertion?

Abstract: Context: The cuff pressure (CP) of the endotracheal tube (ETT) exceeding 30 cm of H 2 O results in reduced perfusion of lateral mucosa of trachea leading to complications. As the posterior tracheal wall is in contact with the esophagus, there is a possibility that the insertion of transesophageal echo (TEE) probe may compress the tracheal wall and increase CP. Aims: This study was aimed to assess the impact of TEE probe insertion on CP in adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…3,4 Various studies has shown that in different periods of TEE insertion and examination, the cuff pressure has increased. In a study done by Borde DP et al 9 The mean cuff pressure increased form baseline 22±3 to 38±10 cm of H 2 O after insertion of probe and to 30±6 cm of H 2 O after TEE examination which were statistically significant. Similar study done by Tan PH et al 7 also found similar results in consistent to our study where mean cuff pressure increased from 27.7±1.5 to 36.2±6.4 cm of H 2 O after TEE probe insertion and 45% (17/38) of patients had a cuff pressure of more than 35 cm of H 2 O.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…3,4 Various studies has shown that in different periods of TEE insertion and examination, the cuff pressure has increased. In a study done by Borde DP et al 9 The mean cuff pressure increased form baseline 22±3 to 38±10 cm of H 2 O after insertion of probe and to 30±6 cm of H 2 O after TEE examination which were statistically significant. Similar study done by Tan PH et al 7 also found similar results in consistent to our study where mean cuff pressure increased from 27.7±1.5 to 36.2±6.4 cm of H 2 O after TEE probe insertion and 45% (17/38) of patients had a cuff pressure of more than 35 cm of H 2 O.…”
Section: Discussionmentioning
confidence: 83%
“…Total 36 patients were taken as our sample size for the study to have 95% confidence interval and power of 90% from previous study done by Borde DP et al 9 After the patient was brought to the operation theatre, standard monitoring such as electrocardiography and pulse oximetry were applied. Invasive blood pressure monitoring line and central venous catheter through right internal jugular vein were inserted under standard aseptic precautions.…”
Section: Methodsmentioning
confidence: 99%
“…The number of patients in the included studies ranged from 13 to 80. Of the ten studies, seven reported on adult patients 24 , 26 , 27 , 30 , 40 42 , two focused on the pediatric population 25 , 28 , and one included both adult and pediatric patients 31 . The median or mean age of patients was between 0.5 and 66.8 years with a male prevalence of 28.3%-86.4%.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies provided the BMI of the participants that ranged from 15.3 to 44.5 kg/m 2 , while this information was unavailable in the other study 25 . Seven studies involved cardiac surgery 24 , 26 , 28 , 31 , 40 42 , two investigated bariatric surgery 27 , 30 , and the other was on esophagogastroduodenoscopy 25 . One study, which examined the change in cuff pressure among patients undergoing endotracheal intubation with single and double lumen ETTs 29 , was split into two (i.e., Kim 2015a, Kim 2015b) to differentiate the study outcomes between the two devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation